(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
In the article, there were many attempts to study the spring and summer development periods of the bee family in the climatic conditions of Uzbekistan. In the conducted studies, it was recognized that there are 3 specific periods in the development of the bee family in the conditions of our republic.